A comparative analysis of the oral microbiome of Amish and non-Amish individuals to strengthen our understanding of variation within the oral microbiome - Debra L. Wohl; Phillip T. Belder; Braxton D. Mitchell (PLoS ONE, 2026)
More than 700 phylotypes associated with the oral cavity collectively comprise the oral microbiome. Study of microbiomes has advanced our understanding of human health. Little is known about the oral microbiome of the Old Order Amish population, a distinct ethnoreligious group who choose to stay separate from mainstream society to preserve their traditional, faith-based way of life. This research was to generate a novel characterization of the Amish oral bacterial microbiome and, using a comparative study design, provide metagenomic analyses of potential variations between generated profiles of the Amish and non-Amish. Next-generation sequencing of 16S rRNA genes of supragingival plaque and saliva samples was used. Analysis between oral health habits from surveys (e.g., fluoride use, frequency of dental visits) and markers within the microbiomes were used to assess the extent of variation due to oral health habits or other factors. Samples were analyzed from 14 Amish and 13 non-Amish individuals. Using non-parametric analyses, alpha and beta diversity were measured to assess core microbiomes, abundance, and sample dissimilarity. Compared to non-Amish, Amish experienced significantly lower frequency of dental visits (p < 0.001) and fluoride use (p < 0.001), but no difference in frequency of teeth brushing (p = 0.198) was observed. Alpha-diversity of observed species differed significantly between Amish and non-Amish samples (H = −3.89, p = 0.002). Beta-diversity which accounted for relative taxon abundance and presence, as well as other metadata such as fluoride use, frequency of dental visits, and teeth brushing indicated, for both saliva and plaque, samples clustered by grouping and their covariates. The five primary phyla typically associated with the oral microbiome were the dominant phyla in both Amish and non-Amish individuals, although Proteobacteria were proportionally fewer in Amish samples. We conclude the oral microbiome between the Old Order Amish and rural non-Amish are distinctly different, which may reflect observed differences in lifestyle and oral health habits.